BENEFITS OF PHYSICAL ACTIVITY CANCER TREATMENT: A REVIEW - dos Santos Alves, Ana Lucia; Borges Lima de Castro, Cássia (Cadernos ESP, 2022)
To present discussions on the main benefits of physical activity or physical exercise as a non-drug intervention in the treatment of cancer, based on the existing bibliography on the subject. Systematic literature review using the following databases: Scielo, Biblioteca Virtual da Saúde, Pubmed, Lilacs and academic google. The strings used were selected according to the MeSH terms, consisting of the following string “physical exercise” or “physical activity” and “cancer treatment” or “neoplasms treatment”. Physical activity and exercise have been shown to have a high correlation with several health benefits for cancer patients, showing evidence that they are methodologies with a high bias of possibilities for interventions. Several benefits can be obtained, regardless of the treatment stage, being it preoperative, postoperative or during chemotherapy and radiotherapy, different positive points can be seen for the inclusion of this practice in conventional treatments.
Keywords: Physical activity; Physical exercise; Cancer; Neoplasms; Treatment